1998
DOI: 10.1094/pdis.1998.82.12.1345
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Pod Rot Pathogens in Peanuts Grown in North Carolina

Abstract: Pod rot diseases historically caused significant losses in peanut production in North Carolina. Advances in the understanding of pod rot diseases and changes in cultural practices minimized losses in the years since 1979. By the early 1990s, however, some peanut growers began to observe pod rot that apparently was not associated with infection by common soilborne pathogens. Incidence of pod rot also was high in research plots used to study conservation tillage methods. Selected farms were surveyed in the fall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Sources of seed samples: Fifty seed samples of mixed cultivars of peanut were collected from commercial markets in different parts of Egypt, including Ismailia, Sharkia and Nobaria, during 1996, 1997and 1998.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sources of seed samples: Fifty seed samples of mixed cultivars of peanut were collected from commercial markets in different parts of Egypt, including Ismailia, Sharkia and Nobaria, during 1996, 1997and 1998.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous Sclerotium species attack peanut plants, causing a considerable loss in yield. S. rolfsii and S. bataticola have been isolated from peanut in Egypt (El-Khadem at al., 1974;El-Akkad, 1982;Porter et al, 1990;Hollowell et al, 1998). The floury rot disease, caused by Verticillium sp., attacks peanut pods at a later stage of maturity and has been isolated from seeds (Frezzi, 1965;Mathur et al, 1975;Melouk et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under favorable environmental conditions, Rhizoctonia pod rot, caused by R. solani, can decrease yield by 22 to 28% (Besler et al, 2003). In fields surveyed in North Carolina for pod rot pathogens over a 3-year period, Hollowell et al (1998) found that Rhizoctonia spp. and Pythium spp.…”
mentioning
confidence: 99%
“…Pod rot was found to cause considerable losses in Israel (Frank, 1968). In North Carolina, pod rot was estimated at 6 to 7% in 1995 and 1996 (Hollowell, et al, 1998). In both North Carolina (Hollowell et al, 1998) and the High Plains of Texas (Wheeler et al, 2006), Rhizoctonia spp.…”
mentioning
confidence: 99%